Hybridization, youth subculture, and the self-making of senior Muslim students in a Philippine Public High School - Lanuza, Gerry (2012)
Public schools are spaces for producing self-disciplined "pedagogized" bodies. But they are also a niche for students to create various subcultures that are different from the official school culture. When Muslim students enroll in public schools they are positioned within these heterogeneous spaces, yet as the present study shows, following the Foucauldian approach that ties culture to power and resistance, Muslim students are also able to create their own "techniques" of self-making that allow them to avoid the panoptic surveillance of the school while also blending, though not completely, with the mainstream culture of the students. This study, by focusing on senior Muslim students, maps out the various subcultural styles within the Makabayan school by relying exclusively on the emic categories of the students.
Includes bibliographical references (pages 69-70).
Keywords: High school students; Muslim students; Muslim youth